English Language Needs for Hotel Service and ESP Program: The Case of Hospitality Vocational Secondary School - Imroatul Ma'fiyah; Sumardiono Sumardiono (Journal of Innovation in Educational and Cultural Research, 2023)
In recent years, the quality of English for Specific Purposes (ESP) programs in vocational secondary schools has been emphasized to improve the English language proficiency of graduates. This study aims to develop an understanding of the English language needs and challenges of the hospitality vocational school program. This examines their perspectives on ESP learning and whether it reflects different English language needs and challenges. A qualitative case study, using data from teachers, students, and hotel practitioners was employed. All practitioners who work in large-scale hotels with international service standards are occupied to enrich English needs related to the hotel industry. The results show that students need effective communication skills related to situational conversations at hotels. They are expected to be professional: either in terms of English material or language skills regarding their particular needs in hotel services. However, both students and teachers felt that their ESP material had not yet addressed the language skills needed in the hospitality industry. Students experienced limitations in vocabulary, language structures as well as pronunciation related to English for hotels. These findings are ultimately expected to provide recommendations for hospitality program stakeholders to accommodate the needs of ESP students and assume teaching methodologies to address these challenges.